Accelerated Move for AI Education in China. (September 2019) - Yang, Xiaozhe
Purpose: This article summarizes recent developments in the use of artificial intelligence (AI) in Chinese education, paying particular attention to the different applications of AI at a number of different levels. The article reviews key government policies and guidelines and suggests a course for future development. Design/Approach/Methods: The article analyzes key government policies relevant to the implementation of AI in Chinese education. Additionally, the article leverages the author's experience as a key member of national information technology curriculum development, which involved participation in the drafting of various curriculum standards and policy documents and discussions with numerous administrative officials, teachers, and researchers. Findings: This article argues that the use of AI in Chinese education varies at different levels. AI implementation is at its early stage in elementary education; more prevalent in higher education, and even more common in the field of civic education. As a result, in multiple dimensions, Chinese students are becoming better trained to face an age of AI and working together to create an informatized education environment. Originality/Value: This article describes how China is searching for the point where top-down system design meets bottom-up applications to chart its own course for the use of AI in education.